Essential Genes of the Parasitic Apicomplexa. Issue 4 (April 2021) - Oberstaller, Jenna; Otto, Thomas D.; Rayner, Julian C.; Adams, John H.
Abstract : Genome-scale mutagenesis screens for genes essential for apicomplexan parasite survival have been completed in three species: Plasmodium falciparum, the major human malaria parasite, Plasmodium berghei, a model rodent malaria parasite, and the more distantly related Toxoplasma gondii, the causative agent of toxoplasmosis. These three species share 2606 single-copy orthologs, 1500 of which have essentiality data in all three screens. In this review, we explore the overlap between these datasets to define the core essential genes of the phylum Apicomplexa. We further discuss the implications of these groundbreaking studies for understanding apicomplexan parasite biology, and we identify promising areas of focus for developing new pan-apicomplexan parasite interventions. Highlights: Major breakthroughs in genome-scale screens for essential genes have recently been completed in the major human malaria parasite P. falciparum and two related parasites P. berghei and T. gondii . Many shared, parasite-specific genes are essential in all three parasites. Shared-essential genes, particularly parasite-specific genes, provide a short list of the most high-value targets for prioritization of new effective interventions against a range of related, important parasitic diseases.